DATA SECURITY RISKS ON SOCIAL MEDIA FOR THE MILITARY - Leli Setyaningrum; Saravia, Luciano; Zainal Syahlan (Yayasan Nusantara Hasana Berdikari, 2025)
Modern military organizations are influenced by the development of information technology that continues to innovate and the demands of speed and accuracy of data and information. The importance of data security in using social media for the military requires security methods with different specifications to protect the confidentiality of data, especially regarding military operations. The use of qualitative methods with a grounded theory approach provides an understanding of the phenomena that are occurring in the research object. The existence of social media to date, cannot be denied based on existing data, has a big influence on the environment and operations in the military, so there is a need for the development of data or social media security methods with special specifications for the military, both in the form of cryptography with the development of encryption algorithms and their descriptions, as well as innovations for special models of data and information security in the military environment.